Kemampuan Pengelolaan Keuangan Mahasiswa Akuntansi Politeknik Negeri Medan - Sabarita Tarigan; Raina Rosanti; Jasa Ginting (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This article discusses the ability of Accounting students of Medan State Polytechnic in managing personal finances which include five main aspects: spending money according to needs, paying obligations on time, planning finances for the future, saving, and setting aside money for personal and family needs. Most students show good ability in financial management, although some still face challenges, such as difficulty saving and managing expenses. This study uses a survey method with a quantitative approach. The results of the study show that the majority of students are in the good to very good category in financial management. This finding reveals that although some students have large pocket money, their financial management behavior is not yet completely ideal, so it requires more awareness in acting financially. The influence of family, environment, and education plays an important role in shaping students' financial habits, where parents are the main factors.